The Impact of Exercise and Virtual Reality Executive Function Training on Cognition Among Heavy Drinking Veterans With Traumatic Brain Injury: A Pilot Feasibility Study - Pennington, David L.; Reavis, Jill V.; Cano, Monique T.; Walker, Erica; Batki, Steven L. (Frontiers in Behavioral Neuroscience, 2022)
Executive function (EF) underlies self-control deficits in alcohol use disorder (AUD) and traumatic brain injury (TBI). Cognitive training is a promising adjunctive treatment targeting TBI- and AUD- related cognitive dysfunction. However, major limitations in the field of cognitive training exist. This pilot study aimed to obtain feasibility data and a preliminary assessment of an enriched virtual reality (VR) EF training (EFT) intervention combined with exercise (NCT03786276). Using an 8-week randomized adaptive design study, 30 AUD treatment seeking U.S. Veterans completed 9 sessions of exercise-only (n=15) or gameplay control (n=15) over 3 weeks, followed by a week-4 repeat assessment in Phase 1. Twenty-three participants completed and moved on to Phase II, where they completed up to 9 sessions of VR-EFT plus exercise and completed a week-8 end-of-study assessment. Primary outcomes included feasibility to retain participants, usability, and satisfaction of using VR-EFT. Secondary and exploratory outcomes included within group assessment of change in cognitive function, alcohol use, alcohol craving, and post-concussive symptoms among the three treatment conditions. VR-EFT was feasible with moderate to high usability and acceptability ratings. Common VR-related adverse effects included dizziness/motion sickness (n = 2/16, 12.5%). The VR-EFT condition was associated with significant improvement in inhibition-switching and visual scanning (both p < 0.05) during Phase II. Exercise-only was associated with significant improvements in cognitive inhibition, cognitive flexibility, reductions in alcohol craving, and number of standard alcohol drinks per week (all p ≤ .05). The gaming-control condition was associated with improvement in cognitive flexibility and visuospatial immediate recall (both p < 0.05) during Phase 1. Recruitment and retention of U.S. Veterans with AUD and TBI into an exercise plus VR-EFT intervention is feasible, but technological barriers may impact usability. VR-EFT was associated with improvement in executive function domains that were targeted in as little as 3-weeks and 9-sessions of VR-EFT exposure. Results are promising and indicate the need for a larger controlled investigation to assess the efficacy of VR-EFT to enhance treatment outcomes among AUD treatment seeking U.S. Veterans with co-occurring AUD and TBI.